The value of magnetic resonance angiography in the evaluation and surgical management of head and neck pathology - Raja Lope Ahmad, Raja Ahmad Al'konee; Wan Leman, Wan Ishlah; Kamarudin, Norie Azilah; Srinovianti , Noerdin (2005)
Objectives; Magnetic resonance angiography (MRA) is recognized as an alternative to conventional angiography due to non-invasive approach and less time consuming. MRA is a safe noninvasive radioimaging technique where it can evaluate the vessels without injecting any contrast agent. Methods; Here we presented few our head and neck lesion with various pathology to illustrate the usefulness of the MRA. Results; MRA has the ability to delineate both the anatomic relationships between head & neck pathology with normal surrounding structures, the tumor vascularity and the tumor feeding vessel. Conclusion; The aim of this scientific presentation is to highlight the clinical applications for MRA in head & neck pathology especially in providing sufficient information to influence therapeutic decisions.